Gene therapy for diabetes mellitus in rats by intramuscular injection of lentivirus containing insulin gene - Oh, Tae Keun; Li, Mei Zi; Kim, Seung Taik (Diabetes research and clinical practice, 2006)
We assessed therapeutic potential of intramuscular insulin gene delivery in a diabetic murine model. The human proinsulin gene cDNA engineered with concensus furin cleavage sequences was inserted into an advanced lentiviral vector that contained CMV early promoter. After injection of concentrated lentiviral vector (3.5 μg p24 Gag antigen) carrying the insulin gene into the thigh muscle, treated rats demonstrated an increase in body weight, increased survivability, attenuated the hyperglycemic response as well as prevented the formation of ketoacidosis. For these reasons, the intraparenchymal injection of lentiviral vectors into the skeletal muscle to ectopically produce insulin may be an easy and therapeutic treatment modality for type 1 diabetes mellitus.